Regional Coleoptera Fauna: Applying Different Methods to Study Species Diversity in a Single Region - Leonid V. Egorov; Sergei V. Dedyukhin; Sergei K. Alekseev; Olga S. Trushitsyna; Alexander B. Ruchin; Aleksey S. Sazhnev; Anna M. Nikolaeva; Mikhail N. Esin; Anatoliy A. Khapugin (Insects)
In order to study regional faunas, one or two methods of studying Coleoptera are often used. However, a comparison of several ways of studying shows that it is more expedient to use more than one of them. Six different methods of catching Coleoptera used in studies of the biodiversity of regional faunas were compared. This research employed pitfall traps (PfT), beer traps (BT), freely hanging flight intercept traps or window traps (FWT), Malaise traps (MT), pan traps (PT), and sweep net (SN). The goal was to assess the effectiveness of these methods in evaluating the biodiversity of this insect group. Studies were conducted from 2011 to 2017 and 2019 to 2023 in the Ryazan region (the central part of European Russia). A total of 27,892 specimens of Coleoptera (927 species from 64 families) were collected. Specifically, 17,659 specimens were collected using PfT (396 species from 36 families), 4971 specimens using BT (146 species from 30 families), 1014 specimens using FWT (221 species from 51 families), 109 specimens using MT (43 species from 16 families), 2220 specimens using PT (357 species from 42 families), and 1919 specimens using SN (265 species from 32 families). The maximum number of families was observed with FWT, while the minimum number of families was registered with MT. Interestingly, the highest number of rare species from both protected lists was obtained using BT and PfT. The Margalef index was higher for Coleoptera collections using PT and PfT, while the largest Shannon index values were recorded for samples using SN and PT. The Berger–Parker index was the highest for catches using BT, which was characterized by the highest dominance of one or more species. In our study, four species of Coleoptera were found that are included in the protected lists of the Russian Federation and 14 species of Coleoptera were listed in the protected species of the Ryazan region. Considering the results of this study, the Coleoptera fauna of the Ryazan region currently accounts for 1674 species.